The Intraoperative cardiac arrest in the prone position in neurosurgery: A reel challenge for the anesthesiologist (International Journal of Scientific Research and Management (IJSRM), 2022)
The Cardiac Arrest in Elective Neurosurgery, is complex and different from other types, as it’s influenced by the patient’s position, the surgical procedure, and the equipment used to fix the skull; we report a case of a patient admitted for lumbar spine surgery in prone position who presented an intraoperative cardiac arrest. chest compressions can be started immediately for prone patients; some studies confirmed the efficacy of back compressions but patients should be turned supine if possible. When defibrillation were necessary in patients ventilated in the prone position, defibrillation should be attempted, as placing the patient in the supine position would take precious minutes and would reduce the chances of successful defibrillation. Evidence is rare when dealing with neurosurgical patients, and more efforts are needed in understanding the etiologies, mechanisms and the specificities of its management.